Design and Implementation of an RFID-Based Smart Parking Control System with Infrared Sensors and Queueing-Theory Traffic Modelling - Hamzah M. Marhoon (Peneliti Teknologi Teknik Indonesia, 2026)
The growing trends in the need for automated and trusted parking control have fostered the enhancement of smart systems that can do effective access control, precise occupancy identification, and effective traffic control. This paper provides both the design, implementation, and analytical evaluation of a low-cost smart parking control system based on Radio Frequency Identification (RFID)- based vehicle authentication, Infrared (IR) sensor-based slot monitoring, and servo-controlled gate actuation based on an Arduino-based embedded architecture. A working prototype is created to exemplify a one-level parking system, where IR sensors are used to detect live availability slots, an RFID module is used to provide authenticated access, and a Liquid Crystal Display (LCD) device is used to show occupants of the slot. In order to come up with a strict performance evaluation, Queueing Theory is adopted by modelling the entrance gate as a service system of M/M/1. This analytical model can be used to measure waiting times, queue time, and system usage quantitatively at different rates of arrival. Measurements conducted during experimental evaluation involve the accuracy of IR detection, RFID authentication latency, servo response time, system reliability, error-rate characterization, and analysis of energy consumption of each hardware component. These results indicate high accuracy in operation, fast authentication, consistent actuation operation, and low power consumption, applicable when a device is compact or battery powered. The queueing-based modelling also substantiates the fact that the system operates efficiently at the levels below saturation points.